TINJAUAN PENGEMBANGAN DESA WISATA RANTIH KOTA SAWAHLUNTO DENGAN PENDEKATAN PARIWISATA BERKELANJUTAN - Abdiani Khairat Nadra (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2021)
The current tourism trend which is changing from mass tourism to alternative tourism, makes village tourism one of the most popular types of tourism, in line with that the government program through the Ministry of Tourism and Creative Economy targets the development of tourism villages to become leading tourism in Indonesia creating opportunities for developing potential tourist attractions into tourism villages, the new and existing tourism villages promoted to become independent tourism villages. Rantih Tourism Village which has been developed since 2010 has the opportunity to be developed into an independent tourism village. This research is descriptive with a qualitative approach. Data collection was done by interview and observation. Research results Rantih Tourism Village already has tourist attractions consisting of natural, cultural and artificial that are attractive and have adequate accessibility and amenities. Currently Rantih Tourism Village is in the Developing stage and towards Forward, Rantih Village has the potential to be developed into an independent and sustainable tourism village, Implementation of development programs towards an independent and sustainable tourism village can be done by innovating on existing products, improving the quality of Human Resources through training programs, as well as more effective promotion through social media.